Evaluasi Rasionalisasi Stasiun Hujan Metode Kagan Rodda dengan Mempertimbangkan Kriteria Penentuan Lokasi Pembangunan Stasiun Hujan - Reza Renaldhy; I Wayan Yasa; Ery Setiawan (Fakultas Teknik, Universitas Brawijaya, 2021)
This study aims to evaluate the rain station rationalization method using Kagan. In its application, the Kagan method can give results in the form of the number of stations and the location of the placement of the rain station network in an area. However, in its application in the field, the recommendation in the form of placement points does not meet the location criteria for the construction of a rain station. The results of the evaluation carried out at WS Sumbawa show that there are 116 rain stations that need to be added, but after being evaluated using Google Earth to see the suitability of the location against the criteria for the location of the rain station construction, only 36 points meet the criteria. To optimize this method, the recommendation points that do not meet the requirements are moved to the nearest water structure location such as a dam, embung or weir, so that 19 points are moved to the nearest water structure and 61 points are not recommended for the construction of a rain station. These results prove that the recommended number and placement points from the rationalization analysis of the Kagan method cannot be directly applied in the field, the recommendations given must be re-evaluated by taking into account the principles in determining the location of rain post construction.